Η μοναξιά των παιδιών με πρώιμο ψυχικό τραύμα: Τι μαθαίνουμε από τις παρατηρήσεις της Anna Freud; - Γαλανάκη, Ε.; Ά Ναυρίδη (Παιδί και Έφηβος: Ψυχική Υγεία και Ψυχοπαθολογία, 2006)
The aim of this study was to collect, present, and discuss Anna Freud's references to the phenomenon of aloneness and loneliness among children-victims of World War II. Those references are included in Anna Freud's observations of parentless children, children who had lived in concentration camps, children who were separated from their parents due to the evacuation of London, etc. All these children were living in the residences founded by Anna Freud and her collaborators in London (Freud & Burlingham, 1944, 1973; Freud & Dann, 1951). Unfortunately, Anna Freud did not utilize those observations for the interpretation of severe early trauma and for the formulation of her developmental theory. Among Anna Freud's observations, various themes on traumatized children's experience of aloneness and loneliness are identified and discussed, the following: type of attachments; separation anxiety in the relationships with parents, siblings, and peers; fear of loneliness; nature of loneliness; inability to be alone; inability to use aloneness constructively; disturbed and non disturbed ways of mastering the fear of loneliness (e.g., attachment, playing, fantasies, defense mechanisms). The discussion points out that aloneness and loneliness among children with such severe early traumas (war, death of parents, separation from parents, hospitalization) constitute extremely painful and deviant experiences, warranting psychotherapeutic intervention. Anna Freud's observations are discussed in the framework of the classic psychoanalytic approaches, as well as some recent empirical investigations on children's experience of aloneness and loneliness.